ʺConceptual and terminological apparatus of the study of multicultural education of future bachelors of primary educationʺ. - Kuznetsova О. (Problems of Engineer-Pedagogical Education, 2024)
The article deals with the issues of conceptual and terminological apparatus of the study of multicultural education of future bachelors of primary education. It is determined that the main condition that will help to prepare for the transfer of multicultural qualities to primary school students is the inclusion of a system of multicultural education in the process of professional training of future bachelors of primary education. The interpretation of certain terms and concepts related to the multicultural education of future bachelors of primary education is analyzed, and clarifications and additions are proposed. Attention is focused on such definitions of concepts as "culture" and "spiritual culture". It is established that in modern scientific and theoretical studies there is no unambiguous interpretation of the definition of these terms. It has been determined that in the system of educational work of a pedagogical higher education institution, the concept of culture, its significance as a cultural process taking place in a multicultural educational environment, is manifested in the possibility of natural expression of one's individuality and ability in cultural self-development and self-determination in the achievements of material and spiritual culture. The attention is focused on the fact that the spiritual culture of the teacher is a necessary component in the process of multicultural education of future bachelors of primary education, as it combines both personal and professional components. A general description of the concept of "multiculturalism" is given. It is determined that the multicultural personality of a future bachelor of primary education has the following characteristics: understanding of the linguistic, cultural, mental diversity of a multicultural society in which representatives of different cultures unite; sense of national identity and awareness of the importance of different national cultures with distinctive traditions and culture; ability to intercultural dialogue in terms of tolerance, humanism, cultural and spiritual values; awareness of the possibility of professional self-realization in a multicultural society. The category of "multicultural competence" is explained. It is noted that in the process of multicultural education, during which the formation of multicultural competence in students of pedagogical universities takes place, it is necessary to implement such a structure and content of this competence that would meet the modern requirements of society and enable representatives of different religions, ethnicities and traditions to successfully solve problems in a multicultural space. It is proved that the conceptual and terminological apparatus of the study of multicultural education of future bachelors of primary education in Ukraine has certain terminological features. This is due to the fact that Ukraine's integration into the European and world educational space expands the boundaries for the professional and pedagogical activities of future bachelors of primary education and provides new opportunities for their self-realization in the multicultural educational space, which in turn fills the process of multicultural education with new elements and definitions